2016
DOI: 10.1111/1744-9987.12405
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Nutritional Status in Maintenance Hemodialysis Patients

Abstract: Nutritional status of hemodialysis (HD) patients is influenced by a multitude of factors and it strongly correlates with morbidity and mortality. The aim of this study was to investigate the influence of seasonal changes on nutritional status in maintenance HD patients. A selected population of 84 adult (40 females and 44 males, aged 68.98 ± 13.45 years) HD (5.94 ± 6.44 years) patients were investigated. Clinical, biochemical and nutritional parameters (BMI, creatinine, urea, serum albumin, total cholesterol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…There was not statistically signi cant difference between season in the DMS and MIS score. These result is in line with result from our previous study (26) were we did not nd seasonal difference in DMS score nor difference between cold and mild months (26). But is important to note that in multivariate analysis MIS was most signi cant positive predictor for FTI and negative predictor for LTI and BCM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was not statistically signi cant difference between season in the DMS and MIS score. These result is in line with result from our previous study (26) were we did not nd seasonal difference in DMS score nor difference between cold and mild months (26). But is important to note that in multivariate analysis MIS was most signi cant positive predictor for FTI and negative predictor for LTI and BCM.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the results from our previous study (26) as well as the results from this study conducted in a mild Mediterranean climate in Dalmatia, South Croatia, we concluded that clinician should pay more attention to seasonal factors when interpreting nutritional status and oxidative stress and planning nutritive intervention for this population of maintenance HD patients. BackgroundThe data obtained in the current study will be available from the corresponding author upon reasonable request after publication of the results on the main research questions.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Albumin and creatinine are biomarkers of kidney function and are routinely included in the diagnosis of chronic kidney disease. In humans, seasonal variation of kidney biomarkers has been identified, with albumin concentrations tending to be highest in winter months 47‐49 and creatinine concentrations highest in summer months 50,51 . In this study, cosinor analysis revealed statistically significant seasonal variation in both albumin and creatinine, with albumin concentrations peaking in autumn months (October and November) and creatinine concentrations peaking in late spring/early summer (May and June) in dogs.…”
Section: Discussionmentioning
confidence: 55%
“…Various clinical and laboratory parameters were found to differ between seasons and previous studies have shown seasonal variations in blood pressure level (21), body mass composition and hydration state (22), interdialytic weight gain (3,23), body weight (24), calcium phosphate metabolism (25), clinical and laboratory variables that re ect nutritional status (26) and even cognitive impairment, depression, sleep disorders and quality of life (27) in maintenance HD patients.…”
Section: Introductionmentioning
confidence: 96%